Eens droomden wij - van Steen, Peter; Maurits, Peter; Metz, Lex (Amsterdam : De Driehoek, 1957)
Bibliotheek Camille Huysmans
Nr. 119 van 200 genummerde en gesigneerde exemplaren
Nederlands
Brochure
Keywords: poëzie; maatschappijkritiek